Influence of Zinc Nitrate Tetrahydrate and PLA/Cu2O Film on ZnO Nanorods Nanogenerator Performance - Yani Anggraeni; Nandang Mufti; Sumera Rafique; Guangda Hu (Frontier Advances in Applied Science and Engineering, 2023)
ZnO nanorods are a 1-D material that can be used as a triboelectric nanogenerator application to harvest energy from the surrounding environment. This research aims to analyze the effect of the ratio of Zinc Nitrate Tetrahydrate and PLA/Cu2O Film on the morphology, crystal phase and electrical properties of the ZnO Nanorods Nanogenerator. ZnO nanorods were grown on stainless steel substrates using a hydrothermal method. Growth was carried out at a temperature of 100oC for 4 hours with varying concentrations of zinc nitrate tetrahydrate of 40 mM, 50 mM, 60 mM, and 70 mM with a fixed concentration of 40 mM hexamethylenetetramine. The XRD test results of ZnO nanorods obtained a hexagonal wurzite crystal structure with lattice parameters a = b = 3.2446 Å and c = 5.1987 Å. The diameter and length of the ZnO nanorods as a result of SEM characterization are 91.66 nm and 563.8 nm in a sample ratio of 1:1; 76.87 nm and 263.3 nm on a sample ratio of 1.25:1; 87.16 nm and 616.16 nm on a sample ratio of 1.5:1; 73.19 nm and 706.9 nm on a sample ratio of 1.75:1. The results of current and voltage measurements on trielectric nanogenerator devices based on ZnO nanorods and PAN polymer were respectively 4.4 µA, 3.8 V; 26.8 µA, 23.3 V; 8.9 µA. 11.9V; and 9.7 µA, 14.7 V. The results show that the smaller the diameter of the ZnO nanorods, the better the efficiency of the resulting nanogenerator.